Penerapan Prinsip (MFN) dalam Regional Comprehensive Economic Partnership dan Dampaknya terhadap Kebijakan Perdagangan Indonesia - Aulia Hidayat, Robby (Magister Kenotariatan, Universitas Jambi, 2024)
In the era of globalisation and trade liberalisation, countries around the world continue to develop forms of international trade cooperation, such as through the Regional Comprehensive Economic Partnership (RCEP) agreement. RCEP involves 15 countries in Asia-Pacific, including 10 ASEAN members and their five major trading partners, with the aim of reducing tariffs and trade barriers and enhancing economic cooperation. The Most-Favoured Nation (MFN) principle in RCEP requires that any trade concession granted to one member country is also granted to all other members. The implementation of MFN can improve Indonesia's market access to RCEP member countries and boost economic growth through exports and foreign investment, although Indonesia must also manage competitive pressures from other member countries. To maximise the benefits of RCEP, Indonesia needs to formulate appropriate policies, including through the implementation of the Job Creation Law to increase domestic investment. This paper explores the application of MFN in RCEP, its implications for Indonesia, and the importance